Peran Pengawasan Fungsional Oleh Pimpinan Terhadap Peningkatan Kinerja Karyawan Di Dinas Ketahanan Pangan, Tanaman Pangan Dan Hortikultura UPT. Perlindungan Tanaman Pangan Dan Hortikultura Provinsi Sumatera Utara - Mutyara Kd Chairunissa Pohan; Muhammad Ikhsan Harahap (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In a company or organization, even in an agency, the leader definitely leads, when he leads, he definitely has subordinates who can help or do more than that, because the leader cannot possibly work alone, but in practice the leader works according to the SOPs and provisions that have been set. There are both acceptable and unacceptable provisions. However, with this policy, where will the company be taken, to a thriving company or even to an era of destruction. Therefore, leaders must carry out supervision in order to create good and correct employee performance. So the aim of this research is to determine the role of functional supervision in improving employee performance. This research uses a qualitative library research method, by looking for materials that discuss the role of functional supervision. The result is that administrative supervision is important so that errors that occur can be corrected immediately. There are 3 (three) steps to achieve this, namely: 1) creation of standards, 2) comparison of standard functions and 3) corrective action. Most importantly, managers can play a role in implementing the supervisor's work in improving employee performance, namely: 1) Interpersonal relationships, including: as a figure, as a leader. ) and as a broker (Gaison Manager). 2) Information person (information role), including: Monitor, information determiner (conveying information from outside to inside) and speaker (informant). 3) Relation to decision making (decision-making role), including: as an entrepreneur, problem solver, resource allocator, and negotiator